2014
DOI: 10.1245/s10434-014-3839-7
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Learning Curve for Team-Based Laparoscopic Pancreaticoduodenectomy

Abstract: In our experience of building an LPD program, the initial ten cases represent the biggest hurdle with respect to operative times. For an experienced teaching center using a staged and team-based approach, LPD appears to offer meaningful reductions in operative time and blood loss within the first 50 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
109
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 14 publications
7
109
0
4
Order By: Relevance
“…The learning curve of LPD was identified in several studies published before (1,(17)(18)(19) (19) also indicated decreased OT and EBL during learning curve, and proposed a staged learning process to surmount learning curve. They believed that learning curve for LPD consisted of a slow and difficult beginning phase, a steep acceleration phase, and finally a plateau phase with slower but continuous improvements.…”
Section: Discussionmentioning
confidence: 97%
“…The learning curve of LPD was identified in several studies published before (1,(17)(18)(19) (19) also indicated decreased OT and EBL during learning curve, and proposed a staged learning process to surmount learning curve. They believed that learning curve for LPD consisted of a slow and difficult beginning phase, a steep acceleration phase, and finally a plateau phase with slower but continuous improvements.…”
Section: Discussionmentioning
confidence: 97%
“…In laparoscopic pancreaticoduodenectomy, Speicher et al [28] reported that 50 cases were required to achieve reduction in OT and blood loss as compared with the open approach.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several single institution series reported on the safety and feasibility of TLP in the setting of several benign and malignant pancreatic pathologies (2)(3)(4). The available literature mainly focuses on two key aspects of TLP, one being the learning curve necessary to master the procedure and the other being the comparison of overall outcomes between TLP and open pancreaticoduodenectomy (OPD) (5)(6)(7). The numerous studies that have focused on TLP learning curve have identified at least three phases: a slow difficult beginning, followed by a rapid improvement that culminates in a plateau phase characterized by a slow but continuous improvement (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The available literature mainly focuses on two key aspects of TLP, one being the learning curve necessary to master the procedure and the other being the comparison of overall outcomes between TLP and open pancreaticoduodenectomy (OPD) (5)(6)(7). The numerous studies that have focused on TLP learning curve have identified at least three phases: a slow difficult beginning, followed by a rapid improvement that culminates in a plateau phase characterized by a slow but continuous improvement (5)(6)(7). Moreover, most studies comparing TLP to OPD suggest that when TLP is performed in center of expertise the oncologic outcome, the complication rate, and the mortality rate are similar to OPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation